2005
DOI: 10.1097/00006231-200510000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of left ventricular ejection fraction by four different methods using 99mTc tetrofosmin gated SPECT in patients with small hearts: correlation with gated blood pool

Abstract: The currently available gated SPECT methods have moderate to poor correlations in addition to wide agreement limits with gated blood pool studies in patients with small hearts. Improvement of these methods to achieve better results in such patients is recommended. The newly developed LMC method yielded better results in the group with small hearts but with low interchangeability with GBP studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…This is consistent with the fi ndings of earlier reports indicating that LVEF can be overestimated in patients with small hearts owing to underestimation of volumes, particularly in end-systolic phase [11]. Eight-frame ECG gating, which we used for G-SPECT data acquisition, is known to underestimate LVEF when compared with the 16-frame gating technique owing to undersampling of the time-volume curve.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with the fi ndings of earlier reports indicating that LVEF can be overestimated in patients with small hearts owing to underestimation of volumes, particularly in end-systolic phase [11]. Eight-frame ECG gating, which we used for G-SPECT data acquisition, is known to underestimate LVEF when compared with the 16-frame gating technique owing to undersampling of the time-volume curve.…”
Section: Discussionsupporting
confidence: 91%
“…Akincioglu et al has excluded patients with a small heart defined as ESV <20 ml, because the main purpose was the evaluation of diastolic phase in their study [9]. It has been known that the values determined by QGS were less accurate for calculating small left ventricular volumes [11,[18][19][20]. At first we intended to exclude the small-heart patients, but we decided to include all of them because the percentage of subjects with a small heart was unexpectedly high in our study population, as high as ~80% for normal female patients particularly in patients in older age groups.…”
Section: Characteristics Of Japanese Populationmentioning
confidence: 99%
“…On the other hand, in patients with a relatively small left ventricular cavity, for instance in women or children, or with left ventricular hypertrophy, the endocardial border may be inaccurately identified, leading to underestimation of the end-systolic volume [46,47]. This causes significant overestimation of the left ventricular ejection fraction, although differences exist in the degree of overestimation using the various available processing algorithms [47,48]. It has been suggested that proper filtering and zooming may reduce the inaccuracy of gated SPECT in these subjects [46,47].…”
Section: Gated Spect Techniquementioning
confidence: 99%